2000
DOI: 10.1111/j.1572-0241.2000.02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Tissue Transglutaminase Elisa: An Innovative Diagnostic Assay for Celiac Disease

Abstract: These results proved that the human tissue transglutaminase-based ELISA represents a cost-effective strategy for identifying both symptomatic and atypical forms of celiac disease and could mean that intestinal biopsy need no longer be the gold standard for diagnosing this clinical condition. Furthermore, early identification and treatment of patients with celiac disease in an outpatient setting could have significant implications for reducing long-term morbidity and can produce major savings in future health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 23 publications
8
96
0
3
Order By: Relevance
“…x, Not assigned. gp tTG or h tTG (20,23). It is generally accepted that the IgA response related to CD (anti-␣-gliadin, anti-reticulin, antiendomysium, and anti-tTG) is more specific than that of IgG (24 -27).…”
Section: Site Of Synthesis Of Anti-ttg Absmentioning
confidence: 99%
See 1 more Smart Citation
“…x, Not assigned. gp tTG or h tTG (20,23). It is generally accepted that the IgA response related to CD (anti-␣-gliadin, anti-reticulin, antiendomysium, and anti-tTG) is more specific than that of IgG (24 -27).…”
Section: Site Of Synthesis Of Anti-ttg Absmentioning
confidence: 99%
“…The scFv libraries were constructed from either PBL or IBL from three untreated adult CD patients with high anti-␣-gliadin and h tTG Ab titers, the latter determined both by anti-endomysium Abs assayed on human umbilical cord sections as well as h tTG ELISA (20). The biopsy materials were obtained from patients undergoing intestinal biopsy to confirm their diagnoses.…”
Section: Library Constructionmentioning
confidence: 99%
“…In general, specificity tends to be higher with human-based assays compared to first-generation assays. 38 The pooled sensitivity and specificity for human-based IgA tissue transglutaminase antibodies (TTG) are both 98%. 14 However, sensitivity (and to a lesser degree specificity) may vary among laboratories.…”
Section: Tissue Transglutaminase Antibodiesmentioning
confidence: 99%
“…The advantages of tTG testing is that the ELISA test eliminates the disadvantages associated with the use of EMA, namely the higher cost, time-consuming protocol which is unsuitable for testing large numbers of samples, the use of monkey esophagus (or human umbilical cord), and the subjective interpretation of the immunofluorescence analysis [15]. Several studies have compared the analytical and clinical utility of commercially available anti-transglutaminase ELISAs assays [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and found that the use of tTG as antigen for CD diagnosis presents an adequate sensitivity and specificity. Therefore, major efforts have been concentrated on developing a tTG-based ELISA, using either the commercially available guinea pig tTG or human recombinant tTG.…”
Section: Biological Markersmentioning
confidence: 99%
“…Second-generation kits using purified human tTG or human recombinant tTG were developed and introduced in routine practice. Several studies compared the firstand second-generation kits and concluded that the human antigens improve assay sensitiv-ity and selectivity [63,[74][75][76]. A third generation of kits using tTG-gliadin peptide complexes as the antigen has also been proposed; however, it seems to have no advantage over human recombinant antigen kits, especially regarding specificity [77,78].…”
Section: Biological Markersmentioning
confidence: 99%